An Acinetobacter non-baumannii Population Study: Antimicrobial Resistance Genes (ARGs) - Adam Baraka; German M. Traglia; Sabrina Montaña; Marcelo E. Tolmasky; Maria Soledad Ramirez (MDPI AG, 2020)
Acinetobacter non-baumannii species are becoming common etiologic agents of nosocomial infections. Furthermore, clinical isolates belonging to this group of bacteria are usually resistant to one or more antibiotics. The current information about antibiotic resistance genes in the different A. non-baumannii species has not yet been studied as a whole. Therefore, we did a comparative study of the resistomes of A. non-baumannii pathogens based on information available in published articles and genome sequences. We searched the available literature and sequences deposited in GenBank to identify the resistance gene content of A. calcoaceticus, A. lwoffii, A. junii, A. soli, A. ursingii, A. bereziniae, A. nosocomialis, A. portensis, A. guerrae, A. baylyi, A. calcoaceticus, A. disperses, A. johnsonii, A. junii, A. lwoffii, A. nosocomialis, A. oleivorans, A. oryzae, A. pittii, A. radioresistens, and A. venetianus. The most common genes were those coding for different β-lactamases, including the carbapenemase genes blaNDM-1 and blaOXA-58. A. pittii was the species with the most β-lactamase resistance genes reported. Other genes that were commonly found include those encoding some aminoglycoside modifying enzymes, the most common being aph(6)-Id, ant(3")-IIa, and aph(3")-Ib, and efflux pumps. All or part of the genes coding for the AdeABC, AdeFGH, and AdeIJK efflux pumps were the most commonly found. This article incorporates all the current information about A. non-baumannii resistance genes. The comparison of the different resistomes shows that there are similarities in the genes present, but there are also significant differences that could impact the efficiency of treatments depending on the etiologic agent. This article is a comprehensive resource about A. non-baumannii resistomes.